2001
DOI: 10.1128/jcm.39.2.750-753.2001
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for Detection of Biofilms on Needleless Connectors Attached to Central Venous Catheters

Abstract: Central venous catheter needleless connectors (NCs) have been shown to develop microbial contamination.A protocol was developed for the collection, processing, and examination of NCs to detect and measure biofilms on these devices. Sixty-three percent of 24 NCs collected from a bone marrow transplant center contained biofilms comprised primarily of coagulase-negative staphylococci.Intravenous (i.v.) access lines (6, 7) and needleless connectors (NCs) (3, 4) have been demonstrated to be a risk factor for blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 6 publications
2
52
0
8
Order By: Relevance
“…1 shows the S. aureus biofilm on a central venous catheter, as confirmed by the presence of both bacterial cells and extracellular polymeric substances. Our data are consistent with others, such as Donlan et al (14), who examined by scanning electron microscopy needleless conectors attached to central venous catheters shown to develop microbial contamination as biofilms. Marrie and Costerton (27) and Marrie et al (28) related that Staphylococcus aureus biofilm has been observed on surfaces ranging from intravascular catheters to pacemaker leads.…”
Section: Resultssupporting
confidence: 93%
“…1 shows the S. aureus biofilm on a central venous catheter, as confirmed by the presence of both bacterial cells and extracellular polymeric substances. Our data are consistent with others, such as Donlan et al (14), who examined by scanning electron microscopy needleless conectors attached to central venous catheters shown to develop microbial contamination as biofilms. Marrie and Costerton (27) and Marrie et al (28) related that Staphylococcus aureus biofilm has been observed on surfaces ranging from intravascular catheters to pacemaker leads.…”
Section: Resultssupporting
confidence: 93%
“…16 There are various methods for biofilm detection. [7][8][9][10][11][12] In this study we evaluated 110 isolates by three screening methods for their ability to form biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of methods have been standardized in various laboratories, each having their own merits. These methods include tissue culture plate (TCP) [7], tube method (TM) [8], Congo red agar method (CRA) [9], bioluminescent assay [10], light or fluorescent microscopic examination [11,12], air-liquid interface coverslip assay [7,8], and scanning electron microscopy (SEM) [13,14]. SEM is an advanced resolution method that provides ultrastructure analysis of biofilms.…”
Section: Introductionmentioning
confidence: 99%